2020
DOI: 10.3389/fbioe.2020.00463
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Micro-Nano Topography Promotes Cell Adhesion and Osteogenic Differentiation via Integrin α2-PI3K-AKT Signaling Axis

Abstract: Surface topography dictates important aspects of cell biological behaviors. In our study, hierarchical micro-nano topography (SLM-AHT) with micro-scale grooves and nano-scale pores was fabricated and compared with smooth topography (S) and irregular micro-scale topography (SLA) surfaces to investigate mechanism involved in cell-surface interactions. Integrin α2 had a higher expression level on SLM-AHT surface compared with S and SLA surfaces, and the expression levels of osteogenic markers icluding Runx2, Col1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 67 publications
1
43
0
Order By: Relevance
“… 6 , 8 , 42 Our previous study demonstrated that the SLM-AHT surface with hierarchical microgroove/nanopore topography could promote preosteoblast MC3T3-E1 cells osteogenic differentiation by enhancing integrin α2-related cell adhesion. 43 In the current study, we revealed that the SLM-AHT surface could not only enhance osteogenic differentiation of PDLSCs but also inhibit adipogenic differentiation. Nevertheless, the mechanotransduction mechanism of SLM-AHT surface directing cell fate remains to be elucidated.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“… 6 , 8 , 42 Our previous study demonstrated that the SLM-AHT surface with hierarchical microgroove/nanopore topography could promote preosteoblast MC3T3-E1 cells osteogenic differentiation by enhancing integrin α2-related cell adhesion. 43 In the current study, we revealed that the SLM-AHT surface could not only enhance osteogenic differentiation of PDLSCs but also inhibit adipogenic differentiation. Nevertheless, the mechanotransduction mechanism of SLM-AHT surface directing cell fate remains to be elucidated.…”
Section: Resultsmentioning
confidence: 53%
“… 10 Then, we upgraded the preparation protocol and fabricated titanium surfaces with microgrooves/nanoporous hierarchical topography by selective laser melting (SLM) combined with alkali heat treatment (AHT), and our preliminary study suggested that this topography might be more effective in promoting the osteogenic differentiation of preosteoblast MC3T3-E1 cells than that of other surfaces. 11 However, the underlying mechanism of hierarchical micro/nanoscale topography-mediated direction of stem cell differentiation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It had been proven that the bioactivity of SLM dental implants, including in vitro mesenchymal stem cells adherence, proliferation, differentiation, and in vivo osseointegration could be improved by the hierarchical micro-nano topography ( Ferraris et al, 2011 , 2019 ; Gulati et al, 2017 ; H. Wang et al, 2018 ; Yu et al, 2018 ). An up to date research had verified that the osteogenesis promoting effect of nanomodified SLM implants was strongly related to the integrin α2-PI3K-AKT signaling axis ( Zheng et al, 2020 ). Today, SLM titanium surfaces could be nanomodified via anodization ( Gulati et al, 2017 ), hydrothermal (H. Wang et al, 2018 ; Yu et al, 2018 ), or inorganic chemical treatments ( Ferraris et al, 2011 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2018;Yu et al, 2018). An up to date research had verified that the osteogenesis promoting effect of nanomodified SLM implants was strongly related to the integrin α2-PI3K-AKT signaling axis (Zheng et al, 2020). Today, SLM titanium surfaces could be nanomodified via anodization (Gulati et al, 2017), hydrothermal (H. Wang et al, 2018;Yu et al, 2018), or inorganic chemical treatments (Ferraris et al, 2011(Ferraris et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Integrin signalling is one of the first steps upon cell attachment and initiates downstream signalling cascades for cellular responses such as cell adhesion, growth, motility, shape, and differentiation 47 . Integrins are transmembrane proteins that modulate cell-biomaterial crosstalk by interacting www.nature.com/scientificreports/ their extracellular domain with the ECM and the intracellular domain with signalling molecules and can be activated by both surface topography [48][49][50] and surface chemistry [51][52][53] . However, it is still under debate whether cells react initially to surface chemistry 54,55 or surface topograpy 55,56 .…”
Section: Discussionmentioning
confidence: 99%